Pregnancy Intendedness in a High-Risk Obstetric Population in a Tertiary Hospital. - Whistance, Douglas (Department of Obstetrics and Gynaecology, 2024)
Study rationale Recent surveys indicate that only about 41% of pregnancies in South Africa are intended. Unintended pregnancies place women and their unborn children at increased risk, especially in settings where there is already high maternal mortality. Objective This study was conducted to assess pregnancy intendedness in an antenatal population of women with perceived high obstetric risk, and to assess contraceptive knowledge and use in this high-risk group of pregnant women. Method This cross-sectional descriptive study assessed pregnancy intendedness in a group of 222 participants, aged 18 years and older, recruited from patients at a tertiary hospital who had one or more past, existing, or new medical or surgical condition that could adversely impact their pregnancy. Participants' medical, surgical, and obstetric history, high risk obstetric factors and gestational age at booking were recorded from their hospital folders. Participants were privately guided through a questionnaire that included questions measuring pregnancy intendedness according to the London Measure of Unplanned Pregnancy (LMUP) and questions about their knowledge, use and access to contraceptive methods. Results The average age of the women was 31.34 years (SD=5.92). LMUP scores indicated that 17.6% of the women had unintended pregnancies, 40.5% were ambivalent while 41.9% of the pregnancies were intended. 40.1% of the women had experienced complications in previous pregnancies with 35.1% of them having a history of miscarriage. A third (33.8%) had two serious health conditions while 16.2% had three or more serious health conditions. Intendedness was found to be significantly linked to relationship status, agreement with a partner to have a baby, and pre-pregnancy health improvements. The respondents had little knowledge of contraceptive methods other than the depot-medroxyprogesterone acetate (DPMA) injectable, the combined oral contraceptive (COC) pill, the sub-dermal implant, and the loop intrauterine device with 76.1%, 26.1%, 13.5% and 4.5% of the women having ever used these respectively. Only 24 women (10.8%) had discussed planning a pregnancy with the doctor/s managing the serious health condition/s for which they had originally been referred to the hospital. Discussion The study findings for intendedness are in line with other data for South Africa and globally, suggesting that intendedness in women at high risk for obstetric complications does not differ from women who are at low risk. Challenges to effective family planning are also well known, with cultural attitudes about fertility, beliefs about contraceptive safety and male partners' lack of support for contraceptive use clearly implicated. Conclusion This study highlights that against the backdrop of these challenges, women who are already medically at risk are placed in situations of even higher risk. There is an urgent need for the reorganization and scale up of family planning services so that they are not isolated from general and specialist practice, are gender-inclusive and become an integral part of the management of chronic disease.